Mobile Display Advertising: Perilaku Niat Pembelian Konsumen pada High Involvement vs Low Involvement Product - Jiwangga Hadi Nata; Aries Kurniawan (Faculty of Economic and Business, 2019)
This study uses the theory of Stimulus-Organism-Response (S-O-R) using a quantitative approach. Sampling using non-probability sampling method, using purposive sampling technique. Respondents in this study were 200 respondents in the purchase intention category in the High Involvement product and also 200 in the Low Involvement product category. The analysis technique used in this study is Partial Least Square (PLS). The results showed that browsing activities on Instagram for both the High and Low Involvement categories of the product had a positive influence on flow conditions, online trust, and purchase intentions. Then online trust in an account on Instagram has a positive influence on flow conditions. Likewise, the flow condition variable and online trust also have an influence on the purchase intention of the latest items on Instagram. There is no difference in consumer behavior towards purchase intentions in the online domain between High and Low Involvement products.